Urgensi Figur Seorang Ayah Sebagai Imam Dalam Keluarga - Gulo, Rezeki; Agus Mawarni Harefa (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The urgency of the head of the family as a priest in the household is the most basic and essential thing that must be understood by a father figure. Nowadays, there are not a few heads of families who do not understand the nature of themselves as priests in their household. The result is that many families lose their way because they have not experienced good spiritual maturity. For this reason, the head of the family is expected to be a true priest in his family. Of the many, one that must be fulfilled by the head of the family to fulfill his responsibility is to guide his family members to become children of God and live like Christ. This study uses a qualitative method with a library approach. The purpose of this research is to examine case studies with a literature approach while at the same time finding solutions as a form of thought offering.